2009
DOI: 10.1061/(asce)ee.1943-7870.0000045
|View full text |Cite
|
Sign up to set email alerts
|

Continuous Plume Monitoring Using Wireless Sensors: Proof of Concept in Intermediate Scale Tank

Abstract: The current practice for monitoring of subsurface plumes involves the collection of water samples from sparsely distributed monitoring wells and laboratory analysis to determine chemical concentrations. In most field situations, cost and time constraints limit the number of samples that could be collected and analyzed for continuous monitoring of large, transient plumes. With the development of wireless sensor networks ͑WSNs͒, that allow sensors to be incorporated into a distributed wireless communication and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
37
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(37 citation statements)
references
References 12 publications
0
37
0
Order By: Relevance
“…Although there are various alternatives leading to many different combinations that could be used potentially to draw samples from p θ | m N , D, I and to evaluate Z m 1 and Z m 1 , we have used instead a single methodology to do both. The methodology that is used in this paper to address both these problems is nested sampling developed by Skilling 28 for the efficient evaluation of the evidence Z for the general case.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Although there are various alternatives leading to many different combinations that could be used potentially to draw samples from p θ | m N , D, I and to evaluate Z m 1 and Z m 1 , we have used instead a single methodology to do both. The methodology that is used in this paper to address both these problems is nested sampling developed by Skilling 28 for the efficient evaluation of the evidence Z for the general case.…”
Section: Methodsmentioning
confidence: 99%
“…2.2 or Z m 1 Step 5, cf. The are a number of options that are available for the computation of the evidences Z m 1 and Z m 1 .…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Our experience collaborating with experts from several disciplines such as environmental science and engineering [Porta et al (2009)], hydrology, and mining has indicated that many applications are interested in raw data from sensor nodes, instead of aggregated data. This motivates us to focus on a common service that can be applied to many sensor applications: raw sensor data collection from all nodes to one centralized server.…”
Section: Introductionmentioning
confidence: 99%